Game Based Learning (GBL) Dalam Meningkatkan Keterampilan Penalaran Mahasiswa Bidang Teknik & Teknologi: Faktor Kebutuhan, Konsep dan Media - Andeni, Afra Nabilah; Trema, Frendy Khan; Amalia, Direstu; Komalasari, Yeti; Nugraha, Minulya Eska (Cipta Kind Publisher, 2024)
Game-based learning (GBL) is one of the learning systems that we often encounter among students these days. GBL utilizes games as a tool to achieve learning objectives where the games presented can be digital games, traditional games, or role-playing games. Previous research or relevant research has a crucial role in a research or scientific article. This research is useful to strengthen the theory and understand the relationship or influence between the variables studied. This article reviews the factors that influence Game Based Learning (GBL) in improving students' reasoning skills, namely needs, concepts and learning media in engineering and technology. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The research methodology used is descriptive qualitative with the results of literature review articles in the form of: 1) needs affect game-based learning (GBL) in improving the reasoning skills of engineering and technology students; 2) concepts affect game-based learning (GBL) in improving the reasoning skills of engineering and technology students; and 3) media affect game-based learning (GBL) in improving the reasoning skills of engineering and technology students. This research is expected to provide a deeper understanding of the important role of reasoning skills in engineering and technology learning, as well as the benefits of GBL to improve these reasoning skills.